A STUDY ON LICHEN PLANUS IN CHILDREN - Neerja Puri; Asha Puri (Our Dermatology Online, 2013)
Introduction: Lichen planus is considered to be rare in children. However, it does not appear to be uncommon in Indian subcontinent. Aims: The study was undertaken to analyse the clinical profile of childhood lichen planus. Material and Methods: We selected 30 children with LP for the study. The children selected were below the age of 14 years of age. Results and Discussion: In our study, it was seen that that the maximum onset of disease was between 5-9 years of age and mean age of children with LP was 6.8 years. The commonest type of LP in children was classical LP seen in 60% children, followed by actinic LP in 20% children. LP hypertrophicus and linear LP were seen in 10% patients each. Nail changes were seen in 10% patients.